Lente térmica diferencial : um novo método para a análise da transição vítrea de polímeros - Rohling, Jurandir Hillmann (2001)
Polymers are carbonic compounds which, like glasses, present the required properties to be used as optical materials. When suitable for optical application the lower cost of fabrication of these materials make them advantageous when compared to the optical glasses. Therefore, considering the technological importance of polymer materials it is desirable to develop new methods of characterization of their physical and chemicaI properties in order to improve the performance of these materiaIs. The glass transition certainly provides information about the structural behavior ofthe investigated sample. The method usually employed to analyze the glass transition is the DifferentiaI Scaning calorimetry (DSC). This technique is qualitative and can not be used to accurately locate the glass transition, specially when it occurs in a wide temperature range. The thermal lens effect is created when an excitation beam passes through the sample and the absorbed energy is converted into heat. This effect, first observed in 1964, is the base for thermal tens technique. Despite the growing interest and the importance of the applications of the photothermal techniques to the polymer area, so far the photothermal measurements have been carried out mostly at near room temperature conditions. The thermal lens method is one of the photothermal techniques which has been shown to be very sensitive for the study of highly transparent materials. Although this method has been widely used in the study of liquid, solid and gases, only in the last two years it has been applied for temperature dependence studies of glasses. Since this technique is an intrinsically remote method the measurements on a sample placed inside a harsh environment presents, in principIe, no extra difficulty. The aim of this work is to introduce the thermal lens technique as a new method to investigate the glass transition of polymer materials. From the thermal lens experiments the temperature dependence of both the thermal diffusivity and the thermal lens signal amplitude, θ, have been determined. Combining the thermal diffusivity data with the specific heat ones obtained by complementary measurements using the thermal relaxation method, the temperature dependence of the therma1 conductivity ofthe sample was also carried out. The TL experiments were performed in polyvinyl chloride(PVC) in the temperature range from 22ºC up to 70°C and in polycarbonate from 22°C up to 170°C. The thermal lens expeciwent were performed using an argon ion laser as the excitation beam and an He-Ne laser as the probe beam. The samples were positioned inside a device with a temperature controller. For the PVC samples the temperature was changed from room temperature up to 67°C, which included the glass transition. For polycarbonate, whose glass transition is around 150°C, the range of temperature was from room temperature up to 190°C. In order to validate and evaluate the sensitivity of the proposed method we have also carried out complementary measurements using differential scanning calorimetry (DSC) for the evaluation of the glass transition temperature. The resnlts for PVC provided the temperature dependence for the thermal diffusivity, specific heat, thermal conductivity and the thermal lens signal amplitude. All of these parameters presented a strong variation in the glass transition temperature range. Their behavior was analyzed through de Debye theory for non isotropic materials. For the polycarbonate, the TL results show the presence of two glass transitions, one of them associated to the pure polycarbonate and the other to the ABS, a compound introduced into the sample in order to improve its mechanical resistance. It is discussed how the experimentally determined TL parameters and its temperature derivative can be used to locating the glass transition in polymers. Comparing the TL data with those derived from conventional differential scanning calorimetry, TL appears to be a more advantageous technique to locate the glass transition in polymers. Finally, it is proposed that the current transient thermal lens method, with minor changes in its experimental configuration, could be adapted to develop a new technique, called differential thermal lens method, especially designed for the investigation of the glass transitions in polymers.